Relationship between positive parenting and cyberbullying perpetration among adolescents: role of self-esteem and smartphone addiction - Kim, Ji Hye; Song, Hye Young; Jung, Gye Hyun (Frontiers in Psychology, 2024)
This cross-sectional study investigated the mediating effect of adolescent self-esteem and smartphone addiction in the relationship between positive parenting and adolescent cyberbullying perpetration The secondary analysis used data from the 2018 Korean Children and Youth Panel Survey. The data on parental positive parenting, adolescent self-esteem, smartphone addiction, and perpetration of cyberbullying of 2,394 Korean adolescents (boys: 1,297, 54.2%) were analyzed. Hayes' PROCESS macro program was used to confirm the mediating role. The results revealed that 26.5% (n=634) of adolescents had experienced perpetration of cyberbullying. Parental positive parenting did not directly relate to cyberbullying perpetration. Adolescent self-esteem and smartphone addiction played a mediating role between positive parenting and adolescent cyberbullying. Therefore, adolescents' individual characteristics and parent/family system characteristics should be considered in policies aimed at preventing adolescent cyberbullying perpetration, preceded by management of appropriate smartphone use. Improving the youth's self-esteem and teaching them how to use smartphones correctly can help prevent cyberbullying perpetration.